An Atypical Cardiac Tale: Malignant Pericardial Effusion in Extragonadal Germ Cell Tumor - Dachlan, Noorsasiwi; Windy, Jubilette; Romolo, Harvey; Kurniawati, Sri Agustini; Cahyanti, Dian; Treswari, Galuh Ayu; Hadiningrat, Raden Belva Devara (http://dharmais.co.id/, 2026)
Introduction: Despite the clinically silent feature of malignant pericardial effusion, if left untreated, it may lead to a life-threatening complication such as cardiac tamponade. This case report highlights an atypical case of pericardial effusion as a complication of a patient with an extragonadal germ cell tumor.Case Presentation: A 19-year-old male presented with breathlessness that worsened when lying flat and a cough. The patient demonstrated sinus tachycardia and low-voltage QRS in electrocardiography. Initially, the chest radiograph only showed a mediastinal mass and pleural effusion, but transthoracic echocardiography eventually revealed a massive pericardial effusion with mildly reduced ejection fraction (40%). Laboratory tests showed elevated β-HCG and LDH levels. A pericardiectomy was performed on this patient, and the biopsy revealed a mediastinal extragonadal germ cell tumor. The patient’s condition improved after the procedure, and the ejection fraction was normalized (67%).Conclusion: Invasion of the pericardium and the resulting malignant pericardial effusion by EGCT is an atypical phenomenon. The silent and nonspecific clinical manifestation, which also often overlaps with other conditions, may pose a challenge for physicians. Echocardiography has shown a pivotal role in helping physicians achieve early detection and timely intervention for malignant pericardial effusion.